Metabolomics discloses potential biomarkers to predict the acute HVPG response to propranolol in patients with cirrhosis. (10th February 2019) - Reverter, Enric; Lozano, Juan J.; Alonso, Cristina; Berzigotti, Annalisa; Seijo, Susana; Turon, Fanny; Baiges, Anna; Martínez‐Chantar, Mari L.; Mato, José M.; Martínez‐Arranz, Ibon; La Mura, Vincenzo; Hernández‐Gea, Virginia; et al.
Abstract: Background: In cirrhosis, a decrease in hepatic venous pressure gradient (HVPG) > 10% after acute iv propranolol (HVPG response) is associated with a lower risk of decompensation and death. Only a part of patients are HVPG responders and there are no accurate non‐invasive markers to identify them. We aimed at discovering metabolomic biomarkers of HVPG responders to propranolol. Methods: Sixty‐six patients with cirrhosis and HVPG ≥ 10 mm Hg in whom the acute HVPG response to propranolol was assessed, were prospectively included. A targeted metabolomic serum analysis using ultrahigh‐performance liquid chromatography coupled to mass spectrometry was performed. Different combinations of 2‐3 metabolites identifying HVPG responders (HVPG reduction > 10%) were obtained by stepwise logistic regression. The best of these model (AUROC, Akaike criterion) underwent internal cross‐validation and cut‐offs to classify responders/non‐responders was proposed. Results: A total of 41/66 (62%) patients were HVPG responders. Three hundred and eighty‐nine metabolites were detected and 177 were finally eligible. Eighteen metabolites were associated to the HVPG response at univariate analysis; at multivariable analysis, a model including a phosphatidylcholine (PC(P‐16:0/22:6)) and a free fatty acid (20:2(n‐6), eicosadienoic acid) performed well for HVPG response, with an AUROC of 0.801 (0.761 at internal validation). The cut‐off 0.629 was the most efficient for overall classification (49/66 patients correctly classified). Two cut‐off values allowed identifying responders (0.688, PPV 84%) and non‐responders (0.384, NPV 82%) with undetermined values for 17/66 patients. Clinical variables did not add to the model. Conclusions: The combination of two metabolites helps at identifying HVPG responders to acute propranolol. It could be a useful non‐invasive test to classify the HVPG response to propranolol.